Ответ(ы) на вопрос:
Гость
[latex]\frac{a^2-9}{2a^2+1}\bullet(\frac{6a+1}{a-3}+\frac{6a-1}{a+3})=\frac{a^2-9}{2a^2+1}\bullet(\frac{(6a+1)(a+3)}{(a-3)(a+3)}+\frac{(6a-1)(a-3)}{(a+3)(a-3)})=\\\\=\frac{a^2-9}{2a^2+1}\bullet\frac{(6a+1)(a+3)+(6a-1)(a-3)}{(a-3)(a+3)}=\frac{a^2-9}{2a^2+1}\bullet\frac{(6a+1)(a+3)+(6a-1)(a-3)}{a^2-9}=\\\\=\frac{(6a+1)(a+3)+(6a-1)(a-3)}{2a^2+1}=\frac{6a^2+18a+a+3+(6a^2-18a-a+3)}{2a^2+1}=\\\\=\frac{12a^2+3+3}{2a^2+1}=\frac{12a^2+6}{2a^2+1}=\frac{6(2a^2+1)}{2a^2+1}=6.[/latex]
Не нашли ответ?
Похожие вопросы